2012
DOI: 10.1177/0022034512446340
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Pain and Jaw-muscle Activity during Sleep

Abstract: This study compared the jaw-muscle electromyographic (EMG) activity during sleep in patients with craniofacial pain (n = 63) or no painful conditions (n = 52) and between patients with tension-type headache (TTH: n = 30) and healthy control individuals (n = 30). All participants used a portable single-channel EMG device (Medotech A/S) for four nights. There was no significant difference in EMG activity between craniofacial pain (24.5 ± 17.9 events/hr) and no painful conditions (19.7 ± 14.5), or between TTH (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 26 publications
2
70
0
3
Order By: Relevance
“…This finding is in accordance with Raphael et al [15] and Yachida et al [43]. It was also shown that there is no association between self-belief and EMG activity with regard to SB.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with Raphael et al [15] and Yachida et al [43]. It was also shown that there is no association between self-belief and EMG activity with regard to SB.…”
Section: Discussionsupporting
confidence: 93%
“…Other factors that may have influenced the EMG recordings are the set-up procedure and that the placement of the EMG electrode may have differed between repeated recordings. 16 In this study, all participants were carefully instructed and trained in the use of the ambulatory EMG device prior to the registrations. In addition, they were all dental/dental hygienist students and showed great interest to the study, which made them promptly try to manage technical problems (e.g., lost electrodes) and compliance issues.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was based on the EMG activity and calculated with risk of type I and type II errors of 5% and 20% respectively and an estimate of the inter-individual variation of EMG measures set to 40% 16 and a minimal relevant difference to detect between the paired observations of 40%. 11 The EMG parameter "bites per hour" was the primary outcome and the other EMG parameters were secondary outcomes.…”
Section: Sample Size Estimation and Selection Of Participantsmentioning
confidence: 99%
“…14) Intermittent mild teeth grinding may be associated with masticatory muscle pain in the morning. 15 Joint sounds are a common finding in general people.…”
Section: Discussionmentioning
confidence: 99%